MEMBANGUN KARAKTER ISLAMI DI ERA GLOBALISASI: TELAAH KONSEPTUAL GLOBALISASI DAN PENDIDIKAN ISLAM - Asti Triash; Ahmad Saiful Aripin; Fajri Ismail; Indah Wiganti; Yuniar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Globalization brings rapid flows of information, technology, and culture, which significantly impact the character formation of the younger generation. This phenomenon requires Islamic education to adapt to global dynamics without neglecting the fundamental values of Islamic teachings. This study aims to conceptually examine the relationship between globalization and Islamic education in the context of developing Islamic character. A review of the literature indicates that globalization presents challenges in the form of shifting values, consumerism, individualism, and moral relativism, all of which have the potential to erode character values. On the other hand, Islamic education plays a strategic role through the strengthening of aqidah (faith), akhlak (morality), and adab (proper conduct), thereby shaping individuals who are resilient, have integrity, and are adaptive to change. The findings emphasize the importance of integrating contextual Islamic educational methods in line with global developments, utilizing technology wisely, and institutionalizing Islamic character values within both formal and non-formal curricula. This study provides a conceptual contribution for educators and policymakers in designing relevant and sustainable Islamic character education strategies in the era of globalization.